2010
DOI: 10.4137/cmt.s4947
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic Acid Once-yearly: What Role in the Prevention of Non-vertebral Osteoporotic Fractures?

Abstract: Osteoporosis is the most common bone disease. Low levels of oestrogens or testosterone are risk factors for primary osteoporosis. The most common cause of secondary osteoporosis is glucocorticoid treatment, but there are many other secondary causes of osteoporosis. Osteoporosis can be secondary to anti-oestrogen treatment for hormone-sensitive breast cancer and to androgen-deprivation therapy for prostate cancer. Zoledronic acid is the most potent bisphosphonate at inhibiting bone resorption. In osteoporosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…15 A study done by Doggrell et al documented 70% reduction in vertebral fracture rate observed with zoledronic acid. [16][17][18] The health outcomes and reduced incidence with zoledronic acid once yearly (HORIZON) Extension trail, used a design with a shorter treatment period (3 years of treatment followed by 3 years of placebo or active extension) and observed that zoledronic acid administered once-yearly significantly prevented non-vertebral Osteoporosis Fractures. 19 Jun Zhang et al in his meta-analysis had documented that longer term intervention, more than 12 months interventions, could gain a better prevention effect for osteoporosis (OR, 95% CI for BMD was 3.35, 2.77-3.92; for fracture was 0.67, 0.54-0.82).…”
Section: Discussionmentioning
confidence: 99%
“…15 A study done by Doggrell et al documented 70% reduction in vertebral fracture rate observed with zoledronic acid. [16][17][18] The health outcomes and reduced incidence with zoledronic acid once yearly (HORIZON) Extension trail, used a design with a shorter treatment period (3 years of treatment followed by 3 years of placebo or active extension) and observed that zoledronic acid administered once-yearly significantly prevented non-vertebral Osteoporosis Fractures. 19 Jun Zhang et al in his meta-analysis had documented that longer term intervention, more than 12 months interventions, could gain a better prevention effect for osteoporosis (OR, 95% CI for BMD was 3.35, 2.77-3.92; for fracture was 0.67, 0.54-0.82).…”
Section: Discussionmentioning
confidence: 99%
“…Yiğitoğlu et al saw meaningful recoveries in lumbar BMD values of two sisters with thalassemia major whom they treated with 4 mg IV zoledronic acid at intervals for 6 years (one of them had several major fractures), and reported durable efficacy during the follow-up period 27 . However, despite positive results favoring zoledronic acid treatment, it should be noted that the frequency of osteonecrosis of the jaw might increase as the dose and frequency of administration increase 10,28 . The recent detection of certain markers in urine and serum of patients with bone diseases has led to better understanding of the pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years there have been persuasive reports indicating the efficacy and tolerability of bisphosphonates in beta-thalassemic patients. Several therapies including calcium, vitamin D, calcitonin, sex steroids, and strontium ranelate provide contribution to bone growth and remodeling [9][10][11] . Furthermore, in recently one phase 2b study was showed that denosumab is a fully human monoclonal antibody against the receptor activator of nuclear factor kappa-B ligand (RANKL) that has been licensed for the treatment of different types of osteoporosis 12,13 .…”
Section: Introductionmentioning
confidence: 99%